Rancang Bangun Aplikasi Penyewaan Alat “Linda Rental” Berbasis Website - Muhammad Reyhan Awliya Sudjana; Bambang Cahyono; Subhan Hartanto (CV MEDAN TEKNO SOLUSI, 2025)
This study aims to improve the quality of service provided by Cv. Linda Lestari. Cv. Linda Lestari offers rental services for various products such as chairs and tables. Cv. Linda Rental rents party equipment for weddings, school farewells and other events. In the implementation of ongoing work at Cv. Linda Lestari, errors often occur in checking the stock of equipment, the number of shipments does not match the number requested by consumers and reports still occur errors because they are still recording manually. By building a party equipment information system at Cv. Linda Lestari can make it easier for consumers to see information related to party equipment at Cv. Linda Lestari, there are no errors in checking the stock of equipment recorded in the data with the equipment available in the warehouse, the equipment sent matches that requested by consumers, there are no differences in recording the return of party equipment and in terms of recording damaged/lost equipment, there are no errors in recording payment transactions and reports due to loss/damage to files.